1950
DOI: 10.1002/hlca.19500330635
|View full text |Cite
|
Sign up to set email alerts
|

Recherches sur la caséine VI. Sur la transformation de la caséine en paracaséine

Abstract: Volumen XXXIII, Fasciculus VI (1950) -So. 215-216.Les fractions para a, impures sont rbunies, dissoutes B 0,3% au p H 6, additionnees de sulfate d'ammonium B , u = 2,2 e t la solution est port6e B 30"

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1951
1951
1969
1969

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Although the interpretation of these experiments is complicated by the unexpected similarity in the effects of low and high ligation of the bile duct and to some extent by variable recoveries of enzyme activity, we conclude that part ofthe peptidase activity in the brush border is attributable to pancreatic proteases, of which chymotrypsin and elastase are probably implicated. The coagulation of milk by the enzyme rennin (EC 3.4.4.3) is considered to be a two-stage process (Cherbuliez & Baudet, 1950). During the primary phase K-casein is hydrolysed by the enzyme (Waugh & Hippel, 1956;Wake, 1959) and then in the presence of Ca2+ the casein micelles are precipitated (Pyne, 1953).…”
Section: Aparicio (Departments Of Biochemistry and Pathology Univermentioning
confidence: 99%
“…Although the interpretation of these experiments is complicated by the unexpected similarity in the effects of low and high ligation of the bile duct and to some extent by variable recoveries of enzyme activity, we conclude that part ofthe peptidase activity in the brush border is attributable to pancreatic proteases, of which chymotrypsin and elastase are probably implicated. The coagulation of milk by the enzyme rennin (EC 3.4.4.3) is considered to be a two-stage process (Cherbuliez & Baudet, 1950). During the primary phase K-casein is hydrolysed by the enzyme (Waugh & Hippel, 1956;Wake, 1959) and then in the presence of Ca2+ the casein micelles are precipitated (Pyne, 1953).…”
Section: Aparicio (Departments Of Biochemistry and Pathology Univermentioning
confidence: 99%
“…The coagulation of milk by the enzyme rennin (EC 3.4.4.3) is considered to be a two-stage process (Cherbuliez & Baudet, 1950). During the primary phase K-casein is hydrolysed by the enzyme (Waugh & Hippel, 1956;Wake, 1959) and then in the presence of Ca2+ the casein micelles are precipitated (Pyne, 1953).…”
Section: )mentioning
confidence: 99%
“…It has been suggested that the /c-casein fraction of whole-casein is associated exclusively with the a-casein. Cherbuliez & Baudet (1950) and Alais, Mocquot, Nitschmann & Zahler (1953) even concluded that only a-casein is altered by rennin, whereas j8-and y-casein are not attacked but are merely co-precipitated unchanged along with the altered a-casein in the presence of Ca ++ . In this connexion, however, it should be noted that the definition of y-casein is not precise.…”
mentioning
confidence: 99%